Raízes do Brasil, entre o tradicional e o moderno : contrapontos à "ética protestante" na interpretação do Brasil - Bartz, Alessandro (2009)
This dissertation interprets the classical writing of the Brazilian social thought Raízes do Brasil (Roots of Brazil), by Sérgio Buarque de Holanda, which was published in 1936. In order to accomplish this, we analyze the essay from its original context and present the environment in which the book arose. Next, we follow the main thematic lines which serve as the foundations for our author. They are: the personalism, the lack of horizontal social organization and ethics of work, the formation under the rural dominance and patriarchal environment, which responds to a confusion between public and private, and a certain "patrimonalism", until we reach the synthesis conception of "homem cordial" (cordial man) as a fetter to the Brazilian modernization. Moreover, we seek for identifying in the main arguments which were developed a specific reading of the "protestant ethics", which helps us confirm a certain distinction between our socio-political, cultural and religious process of formation and the Nordic protestant context. We argument through the eyes of the ambiguity of the cultural choices that the cordial man, as he presents an emotional ethics confronting a rationalizing protestant ethics, is the implicit counterpoint to the "ascetic protestant" of a "Weber(ian)" origin. In the same way, we defend the existence of a tens ion in Raízes do Brasil, which affirms the cordial ethics as traditional and as a fetter to modernization, but, at the same time, as a Brazilian contribution to the civilization.